Peran Dan Strategi Public Relation Dinas Komunikasi Dan Informatika Kota Serang Dalam Membangun Citra Instansi Daerah - Vivi Isri Undayah; Andini Restu Fitriyani; Hana Mauidunnajah; Ivana Putri (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The Communication and Information Service (Diskominfo) has a strategic role in building a positive image of local government agencies. This literature review research aims to analyze the role and strategy of public relations of the Serang City Diskominfo in building an organizational image. The research method uses a descriptive qualitative approach with literature study techniques through the collection and analysis of scientific literature from journals, reference books, and relevant official documents. The study focuses on the concepts of public relations, image management, and communication of government organizations. The results of the study show that the role of public relations of the Serang City Diskominfo includes the functions of internal and external communication, information management, and the formation of public perception. The main strategies used include the development of communication media, periodic publication programs, and persuasive approaches to build public trust. The study concluded that the success of building the image of the agency